The Effect of Giving Methanol Extract from Magrove Leaves Rhizopora Sp. to The Increase of Erythrocite Amount in Anemia In -Vivo - Aini Aini; Jumari Ustiawaty; Rekka Kartini (Jurnal Biologi Tropis, 2022)
This study aims to determine the effect of methanol extract of mangrove leaves Rhizopora sp. on increasing the number of erythrocytes in anemic rats in vivo. This type of research is a laboratory experimental research. The research design used was a post only control group design using a sample of 4 treatments and each treatment with 5 replications. The sample in this study was a sample taken, namely mice aged 3-4 months with a body weight of 20-25 grams. Male mice (Musmusculus L) and mangrove Rhizophora sp. taken from the coastal village of Lembar. This study used two treatments, namely P1 (methanol extract of mangrove leaves 100mg/kgbb and P2 (methanol extract of mangrove leaves 200mg/kgbb), while for positive control (Ferro Fumarate), and negative control (aquadest). sp. to the increase in the number of anemic mice in vivo K-, K+, PI, and P2, respectively, the average number of erythrocytes was 3.55 x 106/mm3, 7.01 x 106 / mm3, 7.848 x 106 / mm3 and 9.056 x 106 / mm 3. The data were obtained using the ANOVA statistical test to determine whether there was a difference in the effective dose of each treatment, it was necessary to continue with the LSD test, the results were not significantly different between K+, P1 and P2 but significantly different from K- which means there was an effect of giving extract Mangrove leaf methanol on increasing the number of erythrocyte anemia in vivo.